Cross-sectional observation study to investigate the impact of risk-based stratification on care pathways for patients with chronic kidney disease: protocol paper. Issue 6 (9th June 2019) - Bhachu, Harjeet Kaur; Cockwell, Paul; Subramanian, Anuradhaa; Nirantharakumar, Krishnarajah; Kyte, Derek; Calvert, Melanie
Abstract : Introduction: Chronic kidney disease (CKD) management in the UK is usually primary care based, with National Institute for Health and Care Excellence (NICE) guidelines defining criteria for referral to secondary care nephrology services. Estimated glomerular filtration rate (eGFR) is commonly used to guide timing of referrals and preparation of patients approaching renal replacement therapy. However, eGFR lacks sensitivity for progression to end-stage renal failure; as a consequence, the international guideline group, Kidney Disease: Improving Global Outcomes has recommended the use of a risk calculator. The validated Kidney Failure Risk Equation may enable increased precision for the management of patients with CKD; however, there is little evidence to date for the implication of its use in routine clinical practice. This study will aim to determine the impact of the Kidney Failure Risk Equation on the redesignation of patients with CKD in the UK for referral to secondary care, compared with NICE CKD guidance. Method and analysis: This is a cross-sectional population-based observational study using The Health Improvement Network database to identify the impact of risk-based designation for referral into secondary care for patients with CKD in the UK. Adult patients registered in primary care and active in the database within the period 1 January 2016 to 31 March 2017 with confirmed CKD will be analysed. The proportion of patients who meet defined risk thresholds will be cross-referenced with the current NICE guideline recommendations for referral into secondary care along with an evaluation of urinary albumin–creatinine ratio monitoring. Ethics and dissemination: Approval was granted by The Health Improvement Network Scientific Review Committee (Reference number: 18THIN061). Study outcomes will inform national and international guidelines including the next version of the NICE CKD guideline. Dissemination of findings will also be through publication in a peer-reviewed journal, presentation at conferences and inclusion in the core resources of the Think Kidneys programme.